(untitled) (Revista de Psicología, 2019)
Job satisfaction is considered an attitude towards job experience. It’s study has gained importance over the past ten years. This paper is a review on job satisfaction which includes conceptual considerations, assessment scales, recent relevant empirical evidence and suggestions for future research.